The Impact of Fines Inclusion Level and Conditioning Temperature on Pellet Quality and Energy Consumption - M. Saensukjaroenphon; Caitlin E. Evans; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
The advantages of pelleted feed can include improved handling, palatability, and nutrient availability. Poor pellet quality, however, can diminish these positive returns and lead to customer complaints. Thus, commercial feed mills may remove fines with a screener after cooling in order to provide a consistent product to customers. There are limited data on the effect of returning pellet fines back to the pellet mill on pellet quality and pellet mill efficiency. The objective of the following 2 experiments was to determine the effect of fines inclusion level and conditioning temperature on pellet quality and energy consumption. Experiment 1 treatments were arranged in a 3 × 2 factorial design of fines inclusion level (0, 10, and 20%) and conditioning temperature (170 and 180°F). Experiment 2 treatments were arranged in a 3 × 2 factorial design of fines inclusion level (0, 10, and 20%) and conditioning temperature (175 and 185°F). The results of Experiment 1 demonstrated there was no interaction between fines inclusion level and conditioning temperature on pellet durability index (PDI) (P>0.348). Increasing conditioning temperature from 170 to 180°F increased (P<0.003) PDI by 0.6 and 4.3% for both the standard and modified methods, respectively. There was a linear increase (P<0.032) in standard and modified PDI as the fines inclusion level increased. The results of Experiment 2 demonstrated that there was an interaction between fines inclusion level and conditioning temperature for modified PDI (P<0.001). When the diets were pelleted at 185°F, increasing the fines inclusion level increased the modified PDI. However, there was no significant difference for modified PDI of the diets with 0, 10, and 20% fines inclusion level when they were pelleted at 175°F. For starch analysis, there was no interaction between fines inclusion level and conditioning temperature on total starch. There was no evidence of difference in total starch between the diets that were pelleted at 175 and 185°F. The total starch was the lowest in the diet with 0% fines (54.11%) followed by the diet with 20% and 10% fines (56.42% and 57.90%), respectively (P= 0.013). For gelatinized starch and cooked starch, there was no interaction between the fines inclusion level and conditioning temperature. Both fines inclusion level and conditioning temperature did not affect gelatinized starch. For energy consumption, there was an interaction (P<0.0001) between fines inclusion level and conditioning temperature. When the diets were pelleted at 185°F conditioning temperature, the diet with 20% fines required significantly more energy during the pelleting process as compared to the diets with 0 and 10%. However, there was no significant difference in energy consumption for diets containing 0, 10, and 20% fines when the diets were pelleted at 175°F conditioning temperature. Therefore, increasing conditioning temperature increased pellet quality. When a diet contained less than 1.5% oil, recirculating fines through the conditioner and pellet die improved pellet quality. However, the 20% inclusion of fines led to occasional roll slips, decreased pellet mill stability, and increased energy usage when the diet was pelleted.
Keywords: pellet fines; conditioning temperature; pellet quality; recycled pellet fines